Effect of human-derived risk in the individual selection of resting sites by brown bear (Ursus arctos) in the Central Alps - Corradini, Andrea; Pedrotti, Luca; Ciolli, Marco; Tattoni, Clara; Bragalanti, Natalia; Groff, Claudio; Falcinelli, Daniele; Cagnacci, Francesca (2019)
Even the largest terrestrial carnivore of Europe, the brown bear (Ursus arctos), must adapt to human presence; its movement, behaviour, and diet are largely influenced by humans. The analysis of brown bear movement data has shown that bears perceive human-related risk differentially in relation to human activity level, season and time of day, and employ a security-food trade-off strategy. In a human-dominated landscape, when displacement is not an option because of habitat limitations and social mechanisms (such as female philopatry), bear mobility may clash with human activity, thus generating conflict and decrease in acceptance. During the moments of lowest mobility, such as during rest, animals have decreased ability to cope with risky situations, and therefore the selection of suitable resting areas is crucial for the long-term survival of individuals. This study aims to investigate the selection of bedding site by GPS radio-collared adult brown bears in a highly heterogeneous human-dominated landscape. Selected animals are part of a long-term GPS monitoring which started in 2006. For the purpose of the study, all GPS locations were resampled at a 3-hour fix rate, and resting sites have been found with an ad-hoc methodology, which has been later validated through field investigations. The expected output will be the evaluation of the different drivers of selection of resting sites (i.e. in relation to human-derived risk and biological needs) at different spatial scales. I will further discuss my findings and implications upon completion of the analysis.